Spatial covariance of ecosystem services and poverty in China. Issue 1 (1st January 2017) - Eigenbrod, Felix; Tang, Zhiyao; Eisner, Stephanie; Flörke, Martina; Zhao, Guanghua
ABSTRACT: Ecosystem services (ESs) are known to be particularly important to the rural poor globally and effective management of such services is argued to be a sustainable pathway out of poverty. However, there is as yet no clear evidence as to how important ESs are for poverty alleviation, partly as there are very few large-scale studies addressing this issue. Here, we examine patterns of spatial covariation of income poverty and provisioning services and biodiversity using county-level data across China ( n = 1924). We conduct our analyses both at the national scale and at the subnational scale. At the national scale, poor counties have significantly lower levels of agricultural provisioning services and water availability, but significantly higher levels of forest-related provisioning services and biodiversity. This finding supports the hypothesis that in general, high levels of poverty co-occur with areas with high levels of non-agricultural ESs. However, in the forest-dominated counties in southern China, low poverty, high densities of forest-related provisioning services and high levels of natural forest cover co-occur. Our results highlight the scale and context dependency of patterns of co-occurrence of poverty and ESs, and the importance of large-scale analyses for understanding the relationships between poverty and ESs.EDITED BY Berta Martín-López